¿Es la estadística econometría o la econometría es estadística? - Mejia Marcatinco, Luis (2008)
Even if econometry students are not well prepared in statistics, students should have a good understanding of econometry to be able to tackle problems that economists have to face. Therefore, econometry students should be able to handle mathemathical simbols and deductive analytical tools.